gajananiari@gmail.com - Gundewadi, Gajanan; Bhimappa, BB; Rudra, Shalini Gaur (Annals of Agricultural Research, 2018)
Attempts to prolong the shelf life of ivy gourd, a medicinally important member of the cucurbitaceaefamily have been made through use of edible coating. Guar gum and alginate coating was appliedat commercial maturity stage. The physiological, textural and sensory parameters for the vegetablesunder storage at room temperature conditions (22 Â± 2ÂºC and 90-95% relative humidity (RH) weremonitored. Edible coating technique was found effective in retarding the physiological maturationand senescence. Guar gum coating was found more effective in reducing PLW (27.5%) and texturalfirmness (31.7%). Acidity of coated ivygourd was found to increase with maturity, however coatedivy gourd retained its fresh like colouration and flavor even after 9 days of storage at ambienttemperatures